2011
DOI: 10.1007/s11103-011-9741-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the rice CDPK-7 in sorghum: molecular and phenotypic analyses

Abstract: Sorghum (Sorghum bicolor (L.) Moench) is an important source for food, feed, and possesses many agronomic attributes attractive for a biofuels feedstock. A warm season crop originating from the semi-arid tropics, sorghum is relatively susceptible to both cold and freezing stress. Enhancing the ability of sorghum to tolerate cold and freezing offers a route to expand the acreage for production, and provides a potential drought avoidance strategy during flowering, an important parameter for protection of yield. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 46 publications
2
22
1
Order By: Relevance
“…Mendelian inheritance of nptII in T1 generation was confirmed by using geneticin resistance analysis of T1 seedlings. Later studies also verified that nptII was an efficient antibiotic marker for transgenic selection (Howe et al 2006;Mall et al 2011;Liu and Godwin 2012). Likewise, the hygromycin phosphotransferase gene ( hpt) conferring hygromycin resistance was also used as a good selectable marker for sorghum transformation (Hagio et al 1991;Carvalho et al 2004;Nguyen et al 2007;Raghuwanshi and Birch 2010).…”
Section: Selectable Marker Genesmentioning
confidence: 93%
“…Mendelian inheritance of nptII in T1 generation was confirmed by using geneticin resistance analysis of T1 seedlings. Later studies also verified that nptII was an efficient antibiotic marker for transgenic selection (Howe et al 2006;Mall et al 2011;Liu and Godwin 2012). Likewise, the hygromycin phosphotransferase gene ( hpt) conferring hygromycin resistance was also used as a good selectable marker for sorghum transformation (Hagio et al 1991;Carvalho et al 2004;Nguyen et al 2007;Raghuwanshi and Birch 2010).…”
Section: Selectable Marker Genesmentioning
confidence: 93%
“…In this respect, Kovtun et al (1998) reported that overexpression of NPK1 gene causes detrimental effects on embryogenesis. Moreover, the constitutive expression of a calcium dependent protein kinases, OsCDPK-7, in sorghum induced apoptotic cell death in transgenic leaves (Mall et al, 2011). Further supporting this hypothesis is that the regeneration frequency for these genotypes is as high as 22 and 16% for Dorado and SPGM94021, respectively (Assem et al, 2014).…”
Section: Analysis Of the Transgenic Plantsmentioning
confidence: 93%
“…To improve sorghum abiotic stress tolerance, HVA1, thaumatin-like protein (TLP), mtld, OsCDPK-7 and TPS1 genes were successfully introduced into sorghum genome (Devi et al, 2004;Gao et al, 2005a;Maheswari et al, 2010;Mall et al, 2011;Yellisetty et al, 2015). In order to make plants more tolerant to stress and restore the cellular balance, transferring a single gene encoding a single specific stress protein, that is, "single-action" genes may not suffice the required tolerance levels.…”
Section: Introductionmentioning
confidence: 99%
“…Sorghum, a Poaceae member related to sugar cane and maize, is the world's fifth most important cereal crop (Mall et al 2011). A genetic analysis revealed that about onethird of the Sorghum genome is similar to rice in gene order and density (Paterson et al 2009).…”
Section: Introductionmentioning
confidence: 99%